Pengembangan Desain Laboratorium Zakat dan Wakaf pada Jurusan Manajemen Zakat dan Wakaf (Studi Kasus Laboratorium POZAWA / Pondok Zakat dan Wakaf Jurusan Manajemen Zakat dan Wakaf FEBI UIN Prof. K.H. Saifuddin Zuhri Purwokerto - Rahmini Hadi; Slamet Akhmadi; Pramudita Hesti Pratiwi (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
The laboratory is a means and a place to support learning activities related to measurement, testing, developing understanding and skills, as well as innovation in accordance with the disciplines and fields of work that exist in universities. Laboratory of Pondok Zakat and Waqf (Lab. POZAWA) FEBI UIN Prof. K.H. Saifuddin Zuhri Purwokerto plays an important role in strengthening student competencies. So it needs to be developed so that it becomes a quality laboratory with high competitiveness and becomes a reference laboratory in the development of Zakat and Waqf Management at the national level. The method used in this research is the analytical-descriptive method, to describe a factual and actual phenomenon, event or event as it was at the time the research was conducted. The results of this study conveyed that the development of the Pondok Zakat and Waqf Laboratory Design (POZAWA Laboratory) was carried out through 6 (six) efforts, including: 1). Procurement of laboratory equipment for complete facilities in the laboratory room, 2). Procurement of laboratory assistants and technicians, 3). Foster Village Development, 4). Development of extension studios (PODCAST or radio) as information channels, 5). Improving the quantity and quality of laboratory services, 6). Creating a laboratory web site. Apart from that, efforts were also made to map fields of cultivation or business and to make strategic alternative decisions